2020
DOI: 10.1016/j.ajic.2020.06.192
|View full text |Cite
|
Sign up to set email alerts
|

Could the COVID-19 pandemic aggravate antimicrobial resistance?

Abstract: Protective adaptive immunity against severe acute respiratory syndrome coronaviruses 2 (SARS-CoV-2) and implications for vaccines. Cureus. 2020;12:e8399.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 6 publications
0
36
0
5
Order By: Relevance
“…Our results confirm that the implementation of antimicrobial stewardship programmes is a pivotal strategy to be urgently adopted in SARS-CoV-2 pandemic settings. 14 …”
Section: Discussionmentioning
confidence: 99%
“…Our results confirm that the implementation of antimicrobial stewardship programmes is a pivotal strategy to be urgently adopted in SARS-CoV-2 pandemic settings. 14 …”
Section: Discussionmentioning
confidence: 99%
“…The abuse of antimicrobials in acute care settings can stimulate the development of MDR strains [ 7 , 11 , 12 , 13 ]. In this sense, a retrospective observational study analysed the bimonthly incidence of carbapenem-resistant Enterobacteriaceae (CRE) colonisation and the incidence of CRE acquisition in an Italian intensive care unit from January 2019 to June 2020 and reported that the incidence of CRE acquisition went from 6.7% in 2019 to 50% in March–April 2020.…”
Section: Discussionmentioning
confidence: 99%
“…To deduce whether these changes were due to COVID-19, we compared the detailed consumption information for the COVID-19 ward and the hospital without the COVID-19 ward. During the pandemic period (weeks [10][11][12][13][14][15][16][17][18][19][20], no difference was shown regarding antimicrobial prescription (700.3 ± 354.8 vs. 781.8 ± 104.0 DDD per 1000 OBD; p = 0.479), even though the antimicrobial use for weeks 16-20 was significantly higher in the COVID-19 ward (Table 1).…”
Section: Antimicrobial Consumptionmentioning
confidence: 95%
See 1 more Smart Citation
“…The prevalence of telemedicine to control antimicrobial stewardship has previously demonstrated an improved selection of antibiotics and decline in resistance [ 84 ]. It is important to collect microbiological data, primarily to classify formerly identified or evolving pathogens linked to secondary co-infections in patients with SARS [ 85 ]. Epidemiological investigations with AMR surveillance systems that endorse the generation of the standard datasets on the efficacy of antimicrobial intercession in COVID-19 patients, particularly in acute stage patients in ICUs, should be sustained [ 86 ].…”
Section: Tackling Measuresmentioning
confidence: 99%